Endoscopically Visualized Lesions, Histologic Findings, and Bacterial Invasion in the Gastrointestinal Mucosa of Dogs with Acute Hemorrhagic Diarrhea Syndrome. (7th November 2013) - Unterer, S.; Busch, K.; Leipig, M.; Hermanns, W.; Wolf, G.; Straubinger, R.K.; Mueller, R.S.; Hartmann, K.
<x xml:space="preserve">Abstract</x> Background Etiology of hemorrhagic gastroenteritis (HGE) syndrome in dogs is unknown and histopathologic and microbial investigations have only been performed post mortem. Objective To identify characteristic intra vitam endoscopic and histologic mucosal lesions, as well as bacterial species, within the mucosa of dogs with HGE. Animals Ten dogs diagnosed with HGE were included. Eleven dogs with gastroduodenoscopy and different intestinal diseases were used as controls for microbial changes. Dogs pretreated with antibiotics or diagnosed with any disease known to cause bloody diarrhea were excluded from the study. Methods In this prospective study, gastrointestinal biopsies were collected from 10 dogs with HGE. Endoscopic and histologic changes were assessed according to WSAVA guidelines. Biopsies from the stomach, duodenum, ileum, and colon were investigated by histology and by immunohistochemistry for the presence of Clostridium spp. and parvovirus. The first duodenal biopsy taken with a sterile forceps was submitted for bacterial culture. Results Acute mucosal lesions were only found in the intestines, not in the stomach. Clostridium spp., identified as Clostridium perfringens in 6/9 cases, were detected on the small intestinal mucosa in all dogs with HGE, either by culture or immunohistopathology. In the control group, C. perfringens could only be cultured in one of 11 dogs. Conclusions and Clinical Importance The results of this study demonstrate an apparent association between C. perfringens and the occurrence of acute hemorrhagic diarrhea. The term "HGE, " which implies the involvement of the stomach, should be renamed as "acute hemorrhagic diarrhea syndrome."